2021
DOI: 10.1186/s12955-021-01857-y
|View full text |Cite
|
Sign up to set email alerts
|

Viability of a MSQOL-54 general health-related quality of life score using bifactor model

Abstract: Background MSQOL-54 is a multidimensional, widely-used, health-related quality of life (HRQOL) instrument specific for multiple sclerosis (MS). Findings from the validation study suggested that the two MSQOL-54 composite scores are correlated. Given this correlation, it could be assumed that a unique total score of HRQOL may be calculated, with the advantage to provide key stakeholders with a single overall HRQOL score. We aimed to assess how well the bifactor model could account for the MSQOL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In a previous study conducted in MS [ 37 ], we found that a bifactor model fit the data well, suggesting that a unidimensional HRQOL score can be computed using the MSQOL-54. By definition, items in the bifactor model load on a general factor and on one group factor only.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…In a previous study conducted in MS [ 37 ], we found that a bifactor model fit the data well, suggesting that a unidimensional HRQOL score can be computed using the MSQOL-54. By definition, items in the bifactor model load on a general factor and on one group factor only.…”
Section: Introductionmentioning
confidence: 69%
“…The overall HRQOL score could be used in clinical practice to provide health professionals and MS patients with feedback on current functioning [ 37 ]. Also, it could be useful to identify patient subgroups—with different levels of disability as well as disease forms—in order to deliver personalized interventions addressing, for example, resilience or self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…MSQoL-54 is a structured self-reported questionnaire including 54 items generating 12 subscales with two summary scores, the physical health composite summary and the mental health composite summary (28). For the primary outcome, we will use the sum of both composite summaries as a total score (30).…”
Section: Primary Outcomesmentioning
confidence: 99%
“…The 4-dimension MSSS measures patients' ability to manage their conditions and overcome their challenges 16 and the 12-dimension MSQOL-54 measures patients' physical and mental health. 17 These instruments are not SM-specific and do not cover all aspects of SM.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of these instruments are the Multiple Sclerosis Self‐Efficacy Scale (MSSS) ‎‎and the Multiple Sclerosis Quality of Life‐54 (MSQOL‐54) scale. The 4‐‎dimension MSSS measures patients' ability to manage their conditions and overcome ‎their challenges 16 and the 12‐dimension MSQOL‐54 measures patients' physical ‎and mental health 17 . These instruments are not SM‐specific and do not cover all aspects of SM.…”
Section: Introductionmentioning
confidence: 99%